Pengaruh Locus of Control, Budaya Paternalistik, Kapasitas Individu, terhadap Keefektifan Penganggaran Partisipatif dan Budgetary Slack dalam Peningkatan Kinerja Manajerial - Apriwandi, Apriwandi (Jurnal Kajian Manajemen Bisnis, 2012)
The purpose of this study tries to examine the existence of locus of control, the capacity of individuals, and paternalistic culture as a moderating variable on participatory budgeting and budgeraty slack in managerial performance improvement by combining the variable capacity of individuals and budgetary slack. The population in this study is the large-scale manufacturing companies, medium, small and contained in the Province of West Sumatra. Sampling was done by purposive sampling, with manager criteria contained in the company's functional areas, and that company managers were given authority to make budget, at least for his work unit. In collecting data obtained by 78 (78%) questionnaires were returned. From 78 quesionnaire, there were 13 questionnaires which could not be analyzed, then only 65 questionnaires which can be further analyzed. The results of this study prove that there is a significant effect of participation budgeting, budgetary slack to improving managerial performance. In addition, the interaction of locus of contol, the capacity of individuals and paternalistic culture.The use of variable interaction and participation in budgetary slack with locus of control and cultural paternalisitk towards improving managerial performance. And than, the absence of interactions of individual capacitybudgetparticipation.Â